Emotional health and spiritual well-being in trauma survivors of natural disasters in Palu, Central Sulawesi, Indonesia: The role of community resilience - Otniel Aurelius Nole; Yulius Yusak Ranimpi; Shauna Fjaagesund (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2025)
Natural disasters struck Palu, Indonesia, on September 28, 2018. Nevertheless, the problem of post-traumatic stress disorder (PTSD) symptoms remains, even though the Palu community builds resilience communally concerning emotional and spiritual conditions. This research aims to investigate the relevance of community resilience to emotional health and spiritual well-being in trauma survivors of natural disasters in Palu. The qualitative research method involved a photovoice approach involving voices from photographs. The seven participants were all residents of Palu and came from areas that had experienced the greatest impact of natural disasters. Data analysis in the research was based on thematic analysis. The research findings are that community resilience is related to emotional health and spiritual well-being based on eight factors: themes related to emotional health are residential, financial, cultural, and capital; while those related to spiritual well-being are supernatural, ritual, social, and moral. The eight factors emphasize interconnected meanings and describe a model of community resilience. The research contributes to the significance of new insights that motivate governments, social institutions, and policymakers in terms of human empowerment, social advocacy, and sustainable development.